Manufatura aditiva da liga reciclada Al-Fe-Cr-Ti formadora de fase quasicristalina - Araújo, Aylanna Priscila Marques de (Universidade Federal de São Carlos, 2020)
The precipitation of quasicrystalline phase in an α-Al dendritic matrix provides Al-based alloys with high mechanical and wear resistance, mainly at high temperatures, which are promising for applications as automotive and aeronautical engine parts. However, to form the quasicrystalline phase, a high cooling rate must be applied during solidification (~103 K/s), which is usually only precipitated in powders and ribbons because of their reduced thickness. Engine parts typically present complex geometry, being fabricated through casting and/or machining processes, with limited design possibilities. An alternative route to produce these components is using additive manufacturing, where the part is built layer by layer, which allows the production of parts with complex geometry and internal channels. Among the additive manufacturing processes, there is Selective Laser Melting (SLM). This process, besides allowing the production of parts with complex geometries and customized density, also allows achieving high cooling rates (up to 105K/s), which would allow, for example, to obtain quasicrystalline phases in Al-based alloys. Taking into this, the present project aimed to investigate the processability of the recycled Al95Fe2Cr2Ti1 quasicrystalline phase former alloy obtained by the SLM process and to understand phase formation and microstructure resulting. A detailed study was made aiming to obtain samples suitable to tensile and compressive tests, containing the quasicrystalline phases. The Al95Fe2Cr2Ti1 powder alloy and also the parts built by SLM were characterized regarding microstructure, thermal and mechanical stability by X-ray diffraction, differential scanning calorimetry, optical microscopy, scanning and transmission electron microscopy, energy dispersive spectrometer, density, mechanical tensile and compressive tests at different temperatures and hardness. The powder presented suitable characteristics for SLM process. Samples with good properties under compression and tensile strength were produced, which ones had a microstructure rich in i-QC phases.
Additive manufacturing of the recycled Al-Fe-Cr-Ti quasicrystalline phase former alloy
Keywords: Fusão seletiva à laser; Manufatura aditiva; Ligas de alumínio; Quasicristais; Reciclagem; Selective laser melting; Additive manufacturing; Aluminium alloys; Quasicrystalline phases; Recycling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA